THU0283 Incremental Costs of Giant Cell Arteritis in France. (9th June 2015) - Pugnet, G.; Costa, N.; Bouscaren, N.; Bourrel, R.; Lapeyre-Mestre, M.; Sailler, L.; Molinier, L.
Abstract : Background: Giant cell arteritis (GCA) is the most frequent primary large-vessel vasculitis in patients aged over 50 years. Common early manifestations include constitutional symptoms, headache, visual loss, polymyalgia rheumatica (PMR), and jaw claudication. The incidence increases with age and is higher in populations of Northern European origin than in those of Mediterranean countries. The incidence of GCA in France is 10 to 20 per 100 000 people older than 50 years. Objectives: The aim of this study is to assess the net costs due to GCA in France and to identify driver costs of this disease. Methods: This retrospective study used an incidence-based approach. Incident GCA patients were identified in the French National Health Insurance System database (SNIIR-AM) from 2005 to 2008. For each case, 6 disease-free age and gender matched-controls were randomly selected. Their resources consumption was recorded over a 5 years period. Costs were estimated from the health insurance perspective. Direct medical, non-medical and indirect costs (i.e. daily benefits) were recorded. GCA patient's costs were compared to control's net costs then we calculated GCA net costs. Results: 103 GCA patients and 606 controls were included. In the first year following the diagnosis, GCA patient's costs were 8, 139€ and control's costs were 3, 661€ (p<0.001), the net GCA costs was 4, 478€. This incremental cost was mainly due to inpatients, medications and paramedical costs, which accounted for 40%, 17% and 16%, respectively. GCA and controls costs decreased during the 5 year follow-up period from 8, 139€ year one to 4, 572€ year five for GCA and from 3, 661€ to 3, 054€ for controls. Conclusions: GCA constitutes a huge economic burden in health insurance expenses. Disclosure of Interest: None declared